2014
DOI: 10.1111/idh.12075
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the oral‐health‐related quality of life of Brazilian children after an educational preventive programme: an 1‐month longitudinal evaluation

Abstract: In the studied sample, an improvement occurred with respect to the severity of disease, intensity and extension of impacts and global ratings of oral health after 1-month follow-up. These results suggest that improving the global transition in health by enhancing coping and management skills while inducing slight changes in the clinical status and the specific aspects of health compromised by the disease is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…42 Therefore, removal of plaque and plaque-derived products, according to many authors, has been a key procedure for treatment of periodontal disease. [8][9][10][11][12] Our results have confirmed that improvement of gums is observed in both studied groups during the first half of the observation period. It can be explained by the "learning effect."…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…42 Therefore, removal of plaque and plaque-derived products, according to many authors, has been a key procedure for treatment of periodontal disease. [8][9][10][11][12] Our results have confirmed that improvement of gums is observed in both studied groups during the first half of the observation period. It can be explained by the "learning effect."…”
Section: Resultssupporting
confidence: 81%
“…9 For instance, a key procedure for treatment of periodontal disease is plaque reduction or elimination by mechanical/chemical means. [8][9][10][11][12] For many cases, mechanical removal of plaque and plaque-derived products 10,11 leads to disease resolution. However, many clinical trials indicate that self-administered plaque control alone, without periodic professional reinforcement, is inconsistent in providing a long-term inhibition of gingivitis.…”
Section: Introductionmentioning
confidence: 99%
“…Published longitudinal studies on OHRQoL have generally focused on changes in their scores due to the consequences of and benefits from therapeutic interventions, for example, after orthodontic dental treatments 29 periodontal treatment; 30 early childhood caries, according to the perceptions of parents; 31 atraumatic restorative treatment; 32 educational preventive programme 33 or dental caries treatment. 34 However, studies evaluating the follow-up of the natural process of change in adolescents' perceptions of their OHRQoL over time is rarely found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha comenzado a experimentar en otros países la realización de programas preventivos en escolares sobre temas de salud oral, evidenciando resultados positivos en los participantes que indujeron pequeños cambios en el estado clínico de su salud oral y estado psicológico. Por lo Impacto de la salud bucal en la calidad de vida de escolares de 11 a 14 años, Licantén, 2013 5 que se puede concluir que los índices clínicos no reflejan adecuadamente el estado de salud oral, ya que no captan la funcionalidad ni el estado psicológico del paciente 15 . De acuerdo con la presente investigación, las mujeres tuvieron mayor cantidad de problemas dentro del listado total de 18, así como un mayor promedio Child-OIDP que los hombres.…”
Section: Discussionunclassified